1992
DOI: 10.1126/science.1411526
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Propagation of Calcium Waves Mediated by Inositol Trisphosphate

Abstract: Two types of calcium (Ca2+) signaling-propagating intercellular Ca2+ waves of increasing intracellular Ca2+ concentration ([Ca2+]i) and nonpropagating oscillations in [Ca2+]i-co-exist in a variety of cell types. To investigate this difference in Ca2+ signaling, airway epithelial cells were loaded with heparin, an inositol 1,4,5-triphosphate (IP3) receptor antagonist, by pulsed, high-frequency electroporation. Heparin inhibited propagation of intercellular Ca2+ waves but not oscillations of [Ca2+]i. In heparin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
283
2
5

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 498 publications
(300 citation statements)
references
References 35 publications
10
283
2
5
Order By: Relevance
“…In most cases, the underlying mechanism was unknown. In other cell types, intercellularly propagating Ca2+ waves have been reported [30,33,34] that probably result from the regenerative production of IP3 by the diffusion of Ca2+ and/or IP3 through gap junctions to neighbouring cells with concomitant Ca2+ release from intracellular stores [2].…”
Section: Discussion Synchronised Ca2+ Spiking Of Density-arrested Nrkmentioning
confidence: 99%
“…In most cases, the underlying mechanism was unknown. In other cell types, intercellularly propagating Ca2+ waves have been reported [30,33,34] that probably result from the regenerative production of IP3 by the diffusion of Ca2+ and/or IP3 through gap junctions to neighbouring cells with concomitant Ca2+ release from intracellular stores [2].…”
Section: Discussion Synchronised Ca2+ Spiking Of Density-arrested Nrkmentioning
confidence: 99%
“…As a general rule, calcium entry through voltage-gated channels in electrically excitable cells (3) or through agonist-receptor interactions in nonexcitable cells, such as epithelial cells, hepatocytes, or oocytes (4), is thought to initiate the CICR process (1,2). Typically, in nonexcitable cells, the binding of an agonist, such as a hormone, a growth factor, or an extracellular matrix, to the corresponding cell surface receptor initiates a series of reactions that end in the activation of phopholipase C (PLC) and the production of the secondary messenger inositol trisphosphate (IP 3 ) (1,2,4).…”
mentioning
confidence: 99%
“…Typically, in nonexcitable cells, the binding of an agonist, such as a hormone, a growth factor, or an extracellular matrix, to the corresponding cell surface receptor initiates a series of reactions that end in the activation of phopholipase C (PLC) and the production of the secondary messenger inositol trisphosphate (IP 3 ) (1,2,4). IP 3 is thought to induce calcium release from the internal endoplasmic reticulum or mitochondria store, and governs the CICR mechanisms that modulate calcium oscillations (1,2,4). However, not all calcium oscillations found in nonexcitable cells are initiated by the PLC-IP 3 pathway (5).…”
mentioning
confidence: 99%
“…In actual bronchi, cilia sweep upward to remove debris from the lungs, but since our model was symmetric in the x and y directions (without strain) we did not expect an overall directionality. The effects of dynamic strain on ciliary motion were not considered in this work, although it has been previously shown that mechanical stimulation leads to intra-and intercellular Ca 2ϩ signaling that would increase ciliary beat frequency (5,56,66). Therefore, the increase in overall infection rate that we see is unlikely to be due to any changes in ciliary beat frequency or coordination.…”
Section: Discussionmentioning
confidence: 87%